2020
DOI: 10.1021/acs.jpcc.9b10535
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Decomposition of Solvents and Additives toward Solid-Electrolyte Interphase Formation in Lithium-Ion Battery

Abstract: The solid-electrolyte interphase (SEI) formed through the reductive decomposition of solvent molecules plays a crucial role in the stability and durability of lithium-ion batteries. Here, we investigate the initial process of SEI formation through reactive force field–molecular dynamics (ReaxFF-MD) simulations and density functional theory (DFT) calculations. ReaxFF-MD is used as a simulation protocol to predict the evolution of SEI components, and products are obtained in good agreement with the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
2
47
1
Order By: Relevance
“…Computational Details for ReaxFF Simulation: Concerning the ReaxFF simulations, the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS 2018) [54] software was used to conduct 5 ps long simulation for one cycle in the HAIR method. To guarantee good energy conservation while ensuring efficient convergence for collisions and smooth reactions, a proper 0.25 fs timestep is chosen in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Computational Details for ReaxFF Simulation: Concerning the ReaxFF simulations, the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS 2018) [54] software was used to conduct 5 ps long simulation for one cycle in the HAIR method. To guarantee good energy conservation while ensuring efficient convergence for collisions and smooth reactions, a proper 0.25 fs timestep is chosen in this work.…”
Section: Methodsmentioning
confidence: 99%
“…From one side, this method has been used to predict the most probable formation mechanisms aiming to clarify the composition of the SEI ( Vollmer et al., 2004 ), and from the other side, it has been used as a determinative sieve to assess the applicability of additives prior to the experimental studies. Density-functional theory (DFT) ( Li et al., 2020 ) and molecular dynamics (MD) ( Wang et al 2020b ) are common computer simulation methods for this purpose ( Wang et al., 2018a ). However, the exact electrochemical behavior of an additive might vary from what was calculated by means of simulation; modeling can help to scratch out the molecules with characteristics far away from requirements and thus can save time and expenses.…”
Section: Assessment and Analysismentioning
confidence: 99%
“…conducted experiments by using an ultrahigh LiFSI-based electrolyte resulting in comparable CEs and cycle stability. Theoretically, although many studies on HC electrolyte at the atomic level have been reported, the comprehensive degradation reaction of electrolyte on a Li metal anode with SEI formation is in debate. Molecular dynamics (MD) simulations have been known to be one of the most powerful methods for exploring complicated reaction processes by tracking MD trajectories. For example, Camacho-Forero compared the behavior of 1 M and 4 M concentration electrolytes with LiFSI and LiTFSI in DME solvent using the ab initio MD (AIMD) process; these theoretical findings indicated that the possible components of the SEI layer depend on the chemical structure of the electrolyte, and LiF was observed as a substance produced by the complete decomposition of LiFSI.…”
mentioning
confidence: 99%